Nanomaterials Based Gas Sensors for SF6 Decomposition Components Detection - Zhang, Xiaoxing; Tang, Ju; Xiao, Song; Zeng, Fuping; Pan, Cheng; Gui, Yingang (IntechOpen, 2017)
The insulating medium used in gas-insulated switchgear is SF6 gas, which has been widely used in substations. Energy generated by discharge will cause the composition of SF6 and generate characteristic component gases. Diagnosing the insulation defect through analyzing the decomposed gases of SF6 by chemical gas sensors is the optimal method due to its advantages. Carbon nanotubes, TiO2 nanotubes and graphene are chosen as the gas-sensing materials to build specific gas sensors for detecting each kind of SF6 decomposed gases and then enhance the gas sensitivity and selectivity by material modification. The properties and preparation methods are introduced in this book. The author studied the micro-adsorption mechanism and macro-gas sensing properties by theoretical calculation and sensing experiment.